Pituitary Apoplexy with Reversible Cerebral Vasoconstrictive Syndrome after Spinal Anaesthesia for Emergency Caesarean Section: An Uncommon Cause for Postpartum Headache. Issue 1 (January 2014) - Mathur, D.; Lim, L. F. M.; Mathur, M.; Sng, B. L.
Pituitary apoplexy is a rare condition involving pituitary necrosis following either pituitary haemorrhage or infarction. Similarly, reversible cerebral vasoconstrictive syndrome is a cerebrovascular disorder characterised by diffuse, multifocal narrowing of cerebral arteries. Both may present with an acute, intense headache and associated neurological deficits. In postpartum women, these conditions should be considered in the differential diagnosis of post-dural puncture headache following regional anaesthesia, as serious morbidity may ensue if they are left untreated. We report the case of a patient who developed pituitary apoplexy during an emergency caesarean section under spinal anaesthesia. It was further complicated by the development of reversible cerebral vasoconstriction syndrome and stroke.